LRH1 Acts as an Oncogenic Driver in Human Osteosarcoma and Pan-Cancer - Song, Yang; An, Weiwei; Wang, Hongmei; Gao, Yuanren; Han, Jihua; Hao, Chenguang; Chen, Lin; Liu, Shilong; Xing, Ying (Frontiers in Cell and Developmental Biology, 2021)
Osteosarcoma (OS) that mainly occurs during childhood and adolescence is a devastating disease with poor prognosis presented by extreme metastases. Recent studies have revealed that liver receptor homolog 1 (LRH-1) plays a vital role in the metastasis of several human cancers, but its role is unknown in the metastasis of OS. In this study, Gene Ontology (GO) enrichment analyses based on high-throughput RNA-seq data revealed that LRH-1 acted a pivotal part in the positive regulation of cell migration, motility, and angiogenesis. Consistently, LRH-1 knockdown inhibited the migration of human OS cells, which was concurrent with the downregulation of mesenchymal markers and the upregulation of epithelial markers. In addition, short hairpin RNAs (shRNAs) targeting LRH-1 inactivated transforming growth factor beta (TGF-β) signaling pathway. LRH-1 knockdown inhibited human umbilical vein endothelial cell (HUVEC) proliferation, migration, and tube formation. Vascular endothelial growth factor A (VEGFA) expression was also downregulated after LRH-1 knockdown. Immunohistochemistry (IHC) revealed that the expression of LRH-1 protein was significantly higher in tumor tissues than in normal bone tissues. We found that high LRH-1 expression was associated with poor differentiation and advanced TNM stage in OS patients using IHC. Based on The Cancer Genome Atlas (TCGA) database, high LRH-1 expression predicts poor survival in lung squamous cell carcinoma (LUSC), kidney renal papillary cell carcinoma (KIRP), and pancreatic adenocarcinoma (PAAD). The downregulation of LRH-1 significantly hindered the migration and motility of LUSC cells. Using multi-omic bioinformatics, the positive correlation between LRH-1- and EMT-related genes was found across these three cancer types. GO analysis indicated that LRH-1 played a vital role in “blood vessel morphogenesis” or “vasculogenesis” in KIRP. Our results indicated that LRH-1 plays a tumor-promoting role in human OS, could predict the early metastatic potential, and may serve as a potential target for cancer therapy.